Optimization on Tribological Behaviour of AA7075/Zirconium Boride Composites Using Taguchi Technique - S. Krishna Mohan; R. Meenakshi Reddy; V. Kamalakar; Pranavan S; M. Amareswar; A. H. Seikh; M. H. Siddique; T. L. Kishore; Bhupender Singh (Advances in Materials Science and Engineering)
The impact of wear factors on composite materials is examined in this article. Stir casting was used to produce AA7075 alloys with varied nano-zirconium boride weight ratios. The dry sliding wear test was done utilizing pin-on-disc test equipment. The L27 orthogonal array was built by Taguchi’s experiments for optimization. We calculated the proportion of responses that could be attributed to the input parameters using SNR and ANOVA. The rate of wear and the frictional coefficient raised with the highest loading level. Load concentration had an extreme impact on wear rate, coefficient of friction, sliding distance, and speed. Nano-zirconium boride particles placed in the matrix alloy prohibited any material loss. Zirconium boride nanoparticles were applied to AA7075 to increase its wear resistance.